Assessment of wave attenuation ability of selected mangrove vegetations of Peninsular Malaysia - Isfarita Ismail (Institut Oseanografi, 2011)
Mangrove forests cover the upper intertidal zones of the tropical and subtropical shorelines. They play an important part in ecological, economical, physical, and geomorphological aspects and also as a flora and fauna habitat. In Malaysia, mangroves grow in the river deltas. This study focuses on three sites; Taiping. Perak (Bruguira species). Tumpat. Kelantan (Nypa fruticans) and Kemaman, Terengganu (Rhizophora species).